Anesthesia for pulmonary veno-occlusive disease: the dilemma and what we should know as anesthesiologists. Issue 30 (24th July 2020) - Foong, Theng Wai; Tan, Pei Shan; Thampi, Swapna; Balakrishnan, Ashokka
Abstract: Introduction: Pulmonary veno-occlusive disease (PVOD) is a rare form of pulmonary hypertension. It is often underdiagnosed or misdiagnosed as idiopathic pulmonary arterial hypertension (PAH). Inappropriate treatment may cause worsening of symptoms which may lead to fatal outcomes. Anesthetic considerations and management for pulmonary hypertension are well described, but few anesthesiologists are aware of the entity of PVOD and its management. Patient concerns: We report a case of PVOD in a 73-year-old female who was on concurrent aspirin and anagrelide, requiring emergent open femoral hernia repair. Diagnosis: PVOD and incarcerated femoral hernia Intervention: Combined spinal-epidural (CSE) was performed to enable the surgery. Outcome: Surgery was completed successfully under central neuraxial anesthesia and the patient remained stable and comfortable throughout, avoiding the need for general anesthesia. Due to the concurrent aspirin and anagrelide therapy, significant bleeding from the CSE puncture site was observed immediately post-operatively. This was resolved with external manual compression and withholding the aspirin and anagrelide. Patient remained well without neurological deficit and was discharged postoperative day seven. Lessons: It is important to differentiate PVOD from PAH due to the controversial use of pulmonary vasodilators in PVOD. Pulmonary vasodilator is commonly used to treat acute pulmonary hypertension in PAH but its usage may lead to pulmonary edema in patients with PVOD. Hence, with no ideal treatment available, the avoidance of general anesthesia is crucial to prevent acute pulmonary hypertensive crisis in patient with PVOD. However, this needs to be weighed against the elevated risk of central neuraxial bleeding when performing a CSE in a patient on concurrent aspirin and anagrelide therapy. Calculated decision-making considering the risks and benefits of all alternatives should be carried out in such a scenario, and measures should be taken in anticipation of the potential consequences of the eventual decision. Conclusion: It is important to differentiate PVOD from PAH. PVOD has unique anesthetic considerations due to the controversial use of pulmonary vasodilators. This case also emphasizes the importance of active anticipation of potential issues and adequate follow up.